Occupational noise annoyance and sensitivity as potential contributors to oxidative stress in metal industry workers - Iraj Alimohammadi; Athena Rafieepour; Azadeh Ashtarinezhad; Agha Fatemeh Hosseini; Seyed Hosein Tabatabaei; Hossein Jafari; Raziyeh Asadi (Scientific Reports)
Abstract Noise is recognized as a psychological stressor that led to noise annoyance, and individual noise sensitivity could play a moderating role. This study aimed to investigate the association between noise annoyance, noise sensitivity, and oxidative stress responses among workers in metal manufacturing industries. A total of 161 workers participated in the study. Demographic data and noise sensitivity were assessed using the Weinstein Noise Sensitivity Scale, while noise annoyance was evaluated via the ISO/TS 15666:2003 questionnaire. Daily noise exposure was measured using a sound level meter. Serum levels of oxidative stress biomarkers, including Malondialdehyde (MDA), Total Antioxidant Capacity (TAC), and 8-hydroxy-2′-deoxyguanosine (8-OHdG), were determined using ZellBio diagnostic kits. Statistical analyses were performed in SPSS v.18, with a significance threshold of 0.05. The mean equivalent noise level was 80.11 ± 11.3 dBA. Among participants, 80.1% reported some degree of noise annoyance, and 74% reported noise sensitivity. No significant association was observed between demographic variables and oxidative stress markers, nor between noise sensitivity or annoyance and induction of oxidative stress. These findings suggest that, under current exposure conditions, subjective reactions to noise, such as annoyance and sensitivity, may not significantly influence oxidative stress, highlighting the need for further investigation into other modulating factors.